2019
DOI: 10.1002/jbmr.3728
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Remodels Bone Transitional Vessels and the Leptin Receptor-Positive Pericyte Network in Mice

Abstract: Intermittent parathyroid hormone (iPTH) is anti‐osteoporotic and affects bone vessels. Transitional capillaries close to the bone surface, which express both endomucin (Edm) and CD31, bear leptin receptor‐expressing (LepR) perivascular cells that may differentiate into osteoblasts. Increased numbers of type H endothelial cells (THEC; ie, Edmhi/CD31hi cells assessed by flow cytometry, FACS) are associated with higher bone formation in young mice. We hypothesized that iPTH administration impacts transitional ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Intermittent PTH is also known to remodel vessels and induces perivascular cells to subsequently migrate to bone surfaces; it is also a strong inducer of bone formation. We wanted to test whether the iDMP/T+;ColGFP− cortical progenitor cells respond to intermittent PTH treatment and whether this would influence bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent PTH is also known to remodel vessels and induces perivascular cells to subsequently migrate to bone surfaces; it is also a strong inducer of bone formation. We wanted to test whether the iDMP/T+;ColGFP− cortical progenitor cells respond to intermittent PTH treatment and whether this would influence bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…They are important in maintaining the haematopoietic niche as depletion of Nestin‐positive cells leads to significant reduction of haematopoietic progenitors . Leptin‐receptor Cre marks a mesenchymal stromal progenitor cell with potential to become predominantly osteoblasts and adipocytes . Although generated postnatally, these cells are quiescent in nature until bone injury occurs which triggers their proliferation and differentiation …”
Section: Introductionmentioning
confidence: 99%
“…The above angiogenic proteins have shown pharmacological potential as osteoanabolic therapies. In addition, a recent study has reported that intermittent parathyroid hormone treatment expands type H ECs and mobilizes perivascular LepR + cells, indicating extrinsic hormonal regulation of type H vessels in relation to MSC-based anti-osteoporotic actions ( Caire et al., 2019 ). Recent studies have also indicated that distinct MSC subsets reside adjacent to type H or type L vessels ( Sivaraj and Adams, 2016 ), e.g., platelet-derived growth factor receptor beta (PDGFRβ) + and NG2 + subpopulations are associated with the type H vasculature ( Kusumbe et al., 2016 ), while the type L sinusoids are surrounded by subpopulations expressing LepR and CXCL12 ( Ding et al., 2012 ; Sugiyama et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the type H endothelium has been revealed as a crucial mediator of bone regeneration and a pharmacological target to counteract bone loss and enhance fracture healing ( Kusumbe et al., 2014 ; Xu et al., 2018 ). Mechanistically, a series of cellular and molecular basis has been reported to regulate type H vessel formation ( Caire et al., 2019 ; Huang et al., 2016 ; Ramasamy et al., 2014 ; Xie et al., 2014 ; Xu et al., 2018 ; Yang et al., 2017 ). Nevertheless, the MSC-mediated regulation of type H vessels is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, leptin receptor‐positive (LepR + ) cells were identified as being perivascular and a major source of the stem cell fraction within the bone marrow. ( 3,15–19 ) Additionally, these LepR + cells were found to express the bone marrow MSC markers PDGFRα and CD51, and to be highly enriched for fibroblast colony‐forming units. Moreover, analyses indicated that LepR + cells in the bone marrow largely overlap with Nestin, an intermediate filament protein that is known as a neural stem/progenitor marker in adult bone marrow.…”
Section: Introductionmentioning
confidence: 99%